2014
DOI: 10.1111/psyp.12234
|View full text |Cite
|
Sign up to set email alerts
|

Facial, verbal, and symbolic stimuli differently affect the right hemisphere preponderance of stimulus‐preceding negativity

Abstract: The present study investigated whether the right hemisphere preponderance of stimulus-preceding negativity (SPN) was affected by different categories of visual feedback stimulus. A time estimation task was performed with facial, verbal, symbolic, and no-feedback conditions. A principal component analysis identified an early component of SPN in addition to a late component that was morphologically similar to the original SPN. Motivational scores in the verbal and facial conditions were higher than that in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 72 publications
(85 reference statements)
1
23
0
Order By: Relevance
“…The early portion of the SPN (the second 1,000 ms of the 5,000‐ to 15,000‐ms delay interval) at electrode Fz was found to be larger in individuals with greater left occipital lobe activation (MNI coordinates −8, −90, −18, which are similar to −24, −92, −10 in the PUN condition of our study, Table ). In a principal component analysis, Ohgami and colleagues () found that the factor corresponding best to the early SPN loaded heavily on activity in the medial occipito‐parietal area. Based on this evidence, we think it likely that fusiform gyrus activity in Experiment 2 could be related to continued processing of the recently presented cues.…”
Section: Discussionmentioning
confidence: 99%
“…The early portion of the SPN (the second 1,000 ms of the 5,000‐ to 15,000‐ms delay interval) at electrode Fz was found to be larger in individuals with greater left occipital lobe activation (MNI coordinates −8, −90, −18, which are similar to −24, −92, −10 in the PUN condition of our study, Table ). In a principal component analysis, Ohgami and colleagues () found that the factor corresponding best to the early SPN loaded heavily on activity in the medial occipito‐parietal area. Based on this evidence, we think it likely that fusiform gyrus activity in Experiment 2 could be related to continued processing of the recently presented cues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, anticipation of verbal and symbolic stimuli increases the amplitude of the late component of SPN, which shows the maximum amplitude during the latter part of the anticipating interval. On the other hand, anticipation of facial stimuli increases the amplitude of the early component of SPN that shows the maximum amplitude during the earlier part of an anticipatory interval 27) . This means that face anticipation is faster than verbal and symbolic stimuli.…”
Section: Right Hemisphere Preponderance Of Spn and Functional Differementioning
confidence: 99%
“…We measured the temporal dynamics of the SPN (i.e. −2000–0 ms) because previous research has demonstrated that different SPN phases may reflect distinct cognitive states ( Moris et al , 2013 ; Ohgami et al , 2014 ; Seidel et al , 2015 ). The RewP was isolated using the difference-score method, which has been recommended in a recent meta-analysis of RewP studies to avoid component overlap ( Sambrook and Goslin, 2015 ).…”
Section: Methodsmentioning
confidence: 99%